2003
DOI: 10.1002/zoo.10082
|View full text |Cite
|
Sign up to set email alerts
|

Gut loading to enhance the nutrient content of insects as food for reptiles: A mathematical approach

Abstract: A variety of commercially raised insects are fed to insectivorous reptiles, but information concerning appropriate diets used to feed these insects is limited. In the present study, house crickets (Acheta domesticus adults and nymphs), mealworms (Tenebrio molitor larvae), and silkworms (Bombyx mori larvae) were fed diets containing graded levels of calcium (Ca) and/or vitamin A-nutrients that are low or absent in most insects. Diets and insects were analyzed for moisture, Ca, phosphorus (P), and vitamin A. For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
68
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(72 citation statements)
references
References 36 publications
4
68
0
Order By: Relevance
“…Calcium levels are typically less than 0.3% dry matter (Barker et al, 1998;Finke, 2002Finke, , 2013Oonincx and van der Poel, 2011;Oonincx and Dierenfeld, 2012;Punzo, 2003). The higher levels of calcium occasionally reported for feeder crickets likely reflect calcium in the gut contents (Barker et al, 1998;Finke, 2003;Hatt et al, 2003;Punzo, 2003). The exoskeleton of most insects is primarily composed of protein and chitin, although some insects have a mineralized exoskeleton in which calcium and other minerals are incorporated into the cuticle (Dashefsky et al, 1976).…”
Section: Mineralsmentioning
confidence: 92%
See 2 more Smart Citations
“…Calcium levels are typically less than 0.3% dry matter (Barker et al, 1998;Finke, 2002Finke, , 2013Oonincx and van der Poel, 2011;Oonincx and Dierenfeld, 2012;Punzo, 2003). The higher levels of calcium occasionally reported for feeder crickets likely reflect calcium in the gut contents (Barker et al, 1998;Finke, 2003;Hatt et al, 2003;Punzo, 2003). The exoskeleton of most insects is primarily composed of protein and chitin, although some insects have a mineralized exoskeleton in which calcium and other minerals are incorporated into the cuticle (Dashefsky et al, 1976).…”
Section: Mineralsmentioning
confidence: 92%
“…The same powder used for pinhead or adult house crickets could therefore have different effects on their chemical composition (Sullivan et al, 2009). Similarly, for gut-loaded insects, size differences could lead to differences in nutrient delivery of smaller versus larger insects (Finke, 2003(Finke, , 2005.…”
Section: Enhancing the Nutrient Composition Of Insects As Food For Inmentioning
confidence: 99%
See 1 more Smart Citation
“…The nutrient and fiber content of house crickets and mealworms has been well documented [Pennino et al, 1991;Barker et al, 1998;Finke, 2002Finke, , 2007. In addition, research has demonstrated that the nutritional quality of cultured insects can be improved by feeding them (gut loading) food that has been fortified with specific minerals and vitamins [Anderson, 2000;Klasing et al, 2000;Finke, 2003;Winn et al, 2003]. However, as far as can be determined, nothing has been reported on the effects of feeding exclusively crickets or mealworms on growth parameters of insectivorous lizards.…”
mentioning
confidence: 98%
“…Knowing the weight of the insects and the amount of food in its gastrointestinal tract might allow zoo nutritionists and veterinarians to use insects to deliver a wide range of other compounds, such as carotenoids and pharmaceuticals (e.g. anthelmintics) to captive insectivores (Finke, 2003). Insect protein is readily available with protein quality values similar to, or slightly higher than fish meat or soybean meal.…”
Section: The Use Of Insects As a Food For Animalsmentioning
confidence: 99%